BRIDGING THE LITERACY GAP WITH INTEGRATED MEDIA: EMPOWERING ELEMENTARY STUDENTS TO THRIVE - Nida Amalia Asikin (Indonesian EFL Journal, 2025)
The extended impact of the two-year pandemic has significantly affected the motivation and literacy skills of elementary students. In response to the government's Merdeka curriculum, prioritizing literacy in the 4.0 era, there is an urgent need for innovative approaches. This study advocates for integrated media, combining ICT with manual tools, to enhance literacy skills and boost motivation. Referencing digital literacy, language learning through screen time, and insights from the Routledge handbook of digital literacies in early childhood (Erstad et.al., 2020), the research integrates various media elements, guided by studies in digital literacy, early childhood education, and the impact of video games on reading comprehension. Implementing qualitative method at Linimasa Elementary School, the study involves fourteen students in three groups, engaging in activities like identifying animal sounds and accurately writing and pronouncing animal names. Research outcomes show that integrated media successfully enhances literacy learning with excitement. The study highlights benefits, including increased confidence, teamwork, strategic thinking, and problem-solving skills among students. In conclusion, this research strongly supports teaching literacy to elementary students through integrated media, providing valuable insights for educators, policymakers, and researchers in advancing literacy education in the digital age.Keywords: Integrated media; Teaching Literacy; elementary; Merdeka curriculum